Fostering Christian Values through Ethnomathematics: A Study on Geometry and Cultural Appreciation in Early Education - Massang, Berdinata; Manoppo, Febri Kurnia (Peneliti.net, 2024)
This study explores the intersection of mathematics, particularly geometry, with spiritual values in Christian education. It poses a fundamental question: Can teaching mathematics also foster character development and enhance cultural appreciation in line with Christian principles? By employing a mixed-methods approach that combines quantitative and qualitative analyses, the study evaluates the effect of this teaching method on children's cognitive abilities and character development. The results indicate that using traditional Minahasa cakes significantly enhances children's grasp of geometric concepts and helps instill cultural values, accounting for a notable 36.9% of the variance in learning outcomes. Ultimately, the research demonstrates how integrating ethnomathematics can build a sense of community and cultural identity among students, while aligning educational practices with Christian values of love and service, thereby supporting holistic development in early childhood education